Service Marketing Mix Strategy Effecting the Perceived Service Quality and Loyalty of Foreign Tourists in Thai Health Tourism - ตระกูลมุกทอง, อารีย์ลักษณ์ (RMUTT Global Business and Economics Review, 2016)
The purpose of this quantitative research is to present the service marketing mix strategy effecting the perceived service quality and loyalty of foreign tourists in Thai health tourism. The 400 representative samples were foreign tourists used the services of private hospitals in the province, a popular tourist destination in the five provinces of Thailand, including Bangkok, Chiang Mai, Udon Thani, Chonburi and Phuket. Foreign Tourists most attention to the perceived service quality factors due to these factors had the highest impact to the loyalty, followed by service marketing mix. Moreover, service marketing mix factors had both direct and indirect effects on loyalty of foreign tourists in Thai health tourism through perceived service quality.